(untitled) (Annals of King Edward Medical University, 2019)
Background: Hemorrhage can occur as a consequence of innumerable conditions. It can lead to hemodynamic compromise and death unless treated promptly. Various traditional medicinal plants are being studied for their effects on hemostasis. Justicia adhatoda is commonly used in Ayurvedic medicine to control both external and internal bleeding such as peptic ulcers, piles, bleeding gums, and menorrhagia. Objective: The objective of this study was to observe the effect of Justicia adhatoda leaf extract on bleeding time in mice. Methods: An experimental study was conducted at PGMI, Lahore. Twenty Swiss albino mice were randomly divided to make four groups. Each group had five animals. Normal saline was administered to Group (I). Group (II) was given 50 mg/kg dose of leaf extract. Group (III) received 100 mg/kg dose of extract and Group (IV) was given 200 mg/kg dose of extract. One hour later, the tail was amputated after anesthetizing the animals. Bleeding time was estimated by gently placing Whatman filter paper on the edge of the incision every 30 seconds. The observation of no adherent blood was defined as bleeding time. Results: Bleeding time decreased in all the extract-treated groups. A maximum decrease was recorded in the group that received 200 mg/kg extract (1.9±1.03 minutes) versus normal control (6.1±2.36 minutes), with p<0.01. Bleeding time decreased to 2.6±1.39 minutes with 100 mg/kg dose, with p<0.05. Conclusion: According to the results of this study, Justicia adhatoda leaf extract is effective in controlling excessive bleeding. However, further work needs to be performed to elucidate the underlying mechanism.